KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGAWASAN MUTU PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR BUNGA AL-QUR`AN ACEH SINGKIL - ., Desriadi (Program Studi Pendidikan Agama Islam, 2017)
This research was motivated by the researcher?s desire to examine the school?s principal ability to lead, supervise, operate the systems, procedures, organizations, businesses and rules under his leadership. Of course, it is required the underlying skills, particularly in the leadership field for the harmony of a school principal?s assignments and roles. Therefore, the researcher proposed the problem that how is the leadership approach conducted by school principal's in supervising the quality of Islamic education studies in SD Bunga Al-Qur`an? From the research, there are three findings: (1) The interpersonal communication of the school principal in supervising the quality of Islamic education studies in SD Bunga Al-Qur`an conducted in various ways, persuasively, administratively, directly and indirectly; (2) Decision-makings by the school principal in supervising the quality of Islamic education studies in SD Bunga Al-Qur`an conducted collectively, and conducted by performing meetings or deliberations previously; (3) The implementation of the reward system in supervising the quality of Islamic education studies in SD Bunga Al-Qur`an conducted to the teachers in SD Bunga Al-Qur`an when there were meetings attended by all teachers, at the beginning of school year, or when there were school activities.